Upaya Penyelesaian Konflik Hukum Terhadap Kasus Tawuran Remaja di Wilayah Hukum Polsek Cinere - Aliya Anjani; Erza Syam Zulni Damario; Imam Luthfi Adinegara; Khadijah Aliyah; Naylah; Sabrina Putri Audrey (CV. ITTC INDONESIA, 2026)
The phenomenon of rioting, particularly involving students and adolescents, has become a serious issue in Indonesia's social life. The numerous cases of student brawls reflect moral decline and weak social supervision, therefore firm action from various parties, particularly law enforcement officers, is required. This study aims to understand the law enforcement process in handling adolescent brawl cases in Cinere and the resolution efforts directed at underage offenders. The research method employed is empirical legal research with a socio-legal approach. Data were collected through in-depth interviews, observations, and document studies at the Cinere Sector Police Office. The results of the study indicate that law enforcement at the Cinere Police Sector has been highly effective due to cooperation between law enforcement officers and the Cinere community through pre-emptive, preventive, and repressive activities. Evidence of successful handling can be seen from socialization activities conducted by community police officers (Bhabinkamtibmas) and intensified regional supervision, which have significantly reduced the number of brawls, even achieving zero cases over the last six months. Furthermore, resolution efforts for underage offenders are carried out through counseling, reporting to parents and schools, as well as implementing diversion and restorative justice based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. If the offender causes serious injury or murder, the case will be processed through police detention or subject to juvenile criminal sanctions in accordance with the classifications of offenses under the Criminal Code (KUHP) and Emergency Law Number 12 of 1951.